Tik Tok sebagai Media Alternatif Pengembangan Mahârah Al-Kalâm dalam Mata Kuliah Tadribat Lughawiyah - Nur, Kholida; Farisha, Farisha (Department of Arabic Education - Faculty of Educational Sciences, 2023)
This research aims to develop the Tik Tok application as a relevant alternative media for students in developing Speaking Skills at Ma’arif University Lampung in Linguistic Exercises course by providing themes and assignments that have been determined by the lecturer. The research method uses a descriptive qualitative approach, data and information are collecting using the Miles and Huberman Model, namely by using data reduction. This article aims to describe the use of Tik Tok media in the Linguistic Exercises course as well as student perceptions regarding its use. Based on the results of questionnaire, 22 students gave very positive responses. That Tik Tok is one of the media in Speaking Skills learning which has a positive value with various advantages which are easy, flexible, cheap, economical and can be increase student creativity, as well as increasing performance and self-confidence in speaking Arabic.